EFEKTIFITAS JOLLY PHONICS DAN PERMAINAN KARTU HURUF UNTUK MENINGKATKAN PENGETAHUAN TENTANG ABJAD DAN KESADARAN FONOLOGIS PADA ANAK TK B DENGAN KEMAMPUAN MEMBACA PERMULAAN YANG RENDAH - Indira Ulfa Bestari; Primatia Yogi Wulandari (PENDIDIKAN SAINS DAN TEKNOLOGI, 2023)
Early reading skills is an important ability for early childhood learner, considering that these skills are the foundation for children to overcome the diffiulties on the next level of education. One of the main predictors of early reading ability are letter knowledge and phonological awareness. Early intervention is known to be very necessary on improving children's low early reading skills. Interventions using the jolly phonics method and picture card games are known to be effective in improving early reading skills, especially in terms of improving alphabet knowledge and phonological awareness, moreover these methods have been known as a fun and interesting methods for improving early reading skills for young children. In this study jolly phonics and alphabet card games were used to improve the early reading skills of children aged 6 years 5 months with low early reading skills. The subject is known to just recognize and know the letters c, o, and s and still lacking on distinguishing letter sounds. This study uses qualitative research design with a single case design. The intervention was carried out for 60 to 90 minutes for 12 sessions. The results show that subject could recognize, mention, and distinguish the sounds of vowels such as (a, i, u, e, o) and consonants such as (b, c, d, m, s, n, k, l, p, t). In conclusion the uses of jolly phonics and alphabet card games increased early reading skills, especially for improving alphabet knowledge and phonological awareness.